Usability of computerized nursing process from the ICNP® in intensive care units - Daniela Couto Carvalho Barra; Grace Teresinha Marcon Dal Sasso; Sônia Regina Wagner de Almeida (SciELO, 2015)
OBJECTIVE To analyze the usability of Computerized Nursing Process (CNP) from the ICNP® 1.0 in Intensive Care Units in accordance with the criteria established by the standards of the International Organization for Standardization and the Brazilian Association of Technical Standards of systems. METHOD This is a before-and-after semi-experimental quantitative study, with a sample of 34 participants (nurses, professors and systems programmers), carried out in three Intensive Care Units. RESULTS The evaluated criteria (use, content and interface) showed that CNP has usability criteria, as it integrates a logical data structure, clinical assessment, diagnostics and nursing interventions. CONCLUSION The CNP is a source of information and knowledge that provide nurses with new ways of learning in intensive care, for it is a place that provides complete, comprehensive, and detailed content, supported by current and relevant data and scientific research information for Nursing practices.